Therapeutic Efficacy of Intranasal N-Acetyl-L-Cysteine with Cell-Penetrating Peptide-Modified Polymer Micelles on Neuropathic Pain in Partial Sciatic Nerve Ligation Mice - Hiroshi Nango; Ai Takahashi; Naoto Suzuki; Takumi Kurano; Saia Sakamoto; Taiki Nagatomo; Toyofumi Suzuki; Takanori Kanazawa; Yasuhiro Kosuge; Hiroko Miyagishi (Pharmaceutics)
Background/Objectives: We previously demonstrated that the intranasal administration of cell-penetrating Tat peptide-modified carrier, PEG-PCL-Tat, improves drug delivery to the central nervous system. This study aimed to evaluate the potential of the post-onset intranasal administration of N-acetyl-L-cysteine (NAC) combined with PEG-PCL-Tat (NAC/PPT) for neuropathic pain. Methods: Neuropathic pain was induced by partial sciatic nerve ligation (PSNL) in mice. Mechanical allodynia was assessed using the von Frey test on days 11–14 post-ligation. NAC or NAC/PPT was intranasally administered after pain onset. Western blotting and immunohistochemistry were conducted to evaluate ionized calcium-binding adapter molecule 1 (Iba-1) expression and microglial activation in the spinal cord. Results: Mechanical allodynia was exacerbated 11 days after the ligation in PSNL mice. The intranasal administration of NAC alone prevented allodynia exacerbation but failed to provide a therapeutic effect against allodynia in PSNL mice. In contrast, NAC/PPT administration ameliorated PSNL-induced tactile allodynia, with maximum efficacy seen 13 and 14 days after ligation. Western blotting demonstrated that Iba-1 levels tended to increase in PSNL mice compared to controls. This trend of increased Iba-1 levels in PSNL mice was attenuated by the administration of NAC/PPT, but not by NAC alone. Immunohistochemistry revealed an increased number of Iba-1-stained microglia in the ipsilateral spinal cord of PSNL mice, which were significantly suppressed by the administration of NAC/PPT. Conclusions: These results suggest that the post-onset intranasal administration of NAC/PPT ameliorates mechanical allodynia by suppressing microglia induction and that intranasal delivery with PEG-PCL-Tat might be a useful tool for the pharmacological management of neuropathic pain.